PENGGUNAAN E-LEARNING ILMO UNTUK MENINGKATKAN MUTU PERKULIAHAN DI FAKULTAS EKONOMI - Asrori, Asrori; Fachrurrozie, Fachrurrozie (Fakultas Ekonomi, Universitas Negeri Semarang, 2011)
This study has objectives to examine empirically the behavior of teachers in accepting the use of e-Learning Ilmo (Learning Increasing Motivation) and ti improve the quality of lectures at Economic Faculty. The respondents of this research were lectures who were the users of e-Learning Ilmo. The data were collected through qustionnaire that was developed based on the construct of the theory of technology acceptance (Davis et al, 1989). The results of hypotheses testing were: (1) The usefulness and ease in using e-Learning Ilmo give positive effect to the lecturersâ interest in using it. (2) the lecturersâ interest in using e-Learning Ilmo gives positive effect which automatically can improve the quality of lectures at Economic Faculty, Unnes. To increase the use of e-Learning Ilmo, it is recommended to (1) make simpler and easier the features of e-Learning in Ilmo, (2) give an e-Learning training intensively and comprehensively for the lecturers. (3) replace some conventional lectures that can not be held as scheduled with E-Learning Ilmo course.